2017
DOI: 10.1002/aic.15731
|View full text |Cite
|
Sign up to set email alerts
|

Yield stress dependency on the evolution of bubble populations generated in consolidated soft sediments

Abstract: Retention of hydrogen bubbles within consolidated soft sediments represents an important safety consideration for the management of legacy nuclear wastes due to the potential for acute gas release. Gas retention sufficiently reduced the bulk density of intermediate yield stress (<800 Pa) sediments for the bed to become buoyant with respect to an aqueous supernatant, potentially inducing Rayleigh-Taylor instabilities. X-ray computed tomography revealed that beds of 7-234 Pa yield stress retained very similar, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 61 publications
(219 reference statements)
3
42
0
Order By: Relevance
“…6,16 Fracture toughness typically diminishes with increased yield stress 17 promoting burrowing within highly consolidated sediments of kiloPascal scale yield stress. Furthermore, another x-ray tomography study by the current authors 11 observed that the largest, most mature bubbles remain static on time-scales of several hours during periods of appreciable chronic gas release from sediments of 7-1112 Pa, implying the existence of a gas release mechanism spanning a broad range of shear yield stress conditions which does not entail macroscopic migration of large individual bubbles. A succession of small partial rollover events 18 was briefly considered to explain the chronic gas release, whereby a region of sediment with a high voidage of sub-millimeter bubbles breaks free of the surrounding bulk material and rises through the bed, however no characteristic disturbances in topography or profile of the bed were apparent from tomographic imaging.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…6,16 Fracture toughness typically diminishes with increased yield stress 17 promoting burrowing within highly consolidated sediments of kiloPascal scale yield stress. Furthermore, another x-ray tomography study by the current authors 11 observed that the largest, most mature bubbles remain static on time-scales of several hours during periods of appreciable chronic gas release from sediments of 7-1112 Pa, implying the existence of a gas release mechanism spanning a broad range of shear yield stress conditions which does not entail macroscopic migration of large individual bubbles. A succession of small partial rollover events 18 was briefly considered to explain the chronic gas release, whereby a region of sediment with a high voidage of sub-millimeter bubbles breaks free of the surrounding bulk material and rises through the bed, however no characteristic disturbances in topography or profile of the bed were apparent from tomographic imaging.…”
Section: Introductionmentioning
confidence: 52%
“…9 The presence of gas bubbles has also provoked research into their impact on the bulk strength and elasticity of marine sediments due to the significant implications for the offshore construction industry. 10 Legacy nuclear waste sludge deposits, for example, at Sellafield, UK 11 and Hanford, USA, 12,13 also experience in situ gas (mainly hydrogen) generation due to corrosion of metallic cladding materials and exposed fuel elements, combined with radiolysis of aqueous liquors by water soluble fission products. Further understanding of gas migration and chronic release is required to mitigate against acute gas release events 13,14 with the potential to present a flammability hazard which could risk a breach of containment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations